HEAL (Health Education Assets Library) (Out of Print) - HEAL Team (Association of American Medical Colleges, 2006)
Abstract Like their counterparts in other disciplines and other nations, most American health sciences educators today are awash with digital information resources. Analysts predict that the population of digital objects on the web will continue to grow exponentially. This explosion of digital resources has been concomitant with increased use of technology tools in teaching and learning more generally, from PowerPoint to learning management systems to comprehensive virtual learning environments. Health sciences educators clearly need the infrastructure, digital resource management services, and training to support the efficient identification, use, and reuse of digital materials in a variety of learning contexts. The Health Education Assets Library (HEAL) was formed to facilitate sharing of multimedia resources in a freely accessible, highly searchable digital library. HEAL's mission is to provide free digital resources of the highest quality that meet the needs of today's health sciences educators and learners, as well as the librarians who serve them. Cited as a model for increasing the efficiency and quality of medical education activities, HEAL currently contains a number of collections of multimedia resources for health sciences undergraduate and professional education, as well as resources for patient and consumer health-more than 21,000 high-quality health sciences learning assets and objects in all. As of December 2005, there are over 4,400 registered HEAL users worldwide. With crucial grants from the National Science Foundation under the National Science Digital Library program and the National Library of Medicine, HEAL has successfully established a comprehensive digital library infrastructure, including standards, policies, applications, and a high-quality collection of teaching materials.